B House - Beranda. Cachagua, Chile (2011)
Presentación gráfica de la obra.
Keywords: KLOTZ, MATHIAS; CHILE; REGIÓN VALPARAÍSO; CACHAGUA; VIVIENDAS UNIFAMILIARES; VIVIENDAS SUBURBANAS; VIVIENDAS EN LA COSTA; VIVIENDAS DE MONTAÑA; CONSTRUCCION EN PENDIENTE; CONSTRUCCION; ESTRUCTURAS DE HORMIGON; CERRAMIENTOS; VIDRIO; REVESTIMIENTOS; PIEDRA